A Comparative Randomized Clinical Study of Arthroscopic Anterior Cruciate Ligament Reconstruction with Patellar Tendon and Hamstring Tendon Autologous Grafts - Haider Ali, Azlan Bashir, Adnan Qamar, Usman Amjad, Saad Sultan Rana, Shafqat Raza, Syed Wasif Ali Shah, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine and compare differences in the results following arthroscopic anterior cruciate ligament reconstruction using patellar-tendon-bone (PTB) auto-grafts and hamstrings tendon auto-grafts. Study design: Randomized controlled trial. Place and duration: Department of Orthopedic Surgery, Shaikh Zayed Hospital Lahore from July 2019 to July 2021. Methodology: This prospective study included 72 of total patients with clinical diagnosis of having anterior cruciate ligament (ACL) tear who did not have activities like a healthy person and wished to maintain a level of activity as it was before injury. Institutional ethical committee granted approval and a written informed consent was taken. Two groups of study population (patellar tendon and hamstring tendon) were formed. Lottery method was used for randomization of patients. Arthroscopic ACL reconstruction was done according to their respective groups. Patients of patellar tendon group (n=36) and hamstring tendon group (n=36) were under examination for 4 to 5 days and to grant 0 to 900 movement, knee brace was locked. Patients were questioned about their activities on follow up visits. Results: No significant difference amongst patients of two groups was noted.14 patients (38.9%) with PTB graft were unable to kneel on their knee as compared to 12 patients (33%) with hamstrings graft. Patients with BTB graft had similar difficulty in bending their knee as compared to the patients of the other group. Conclusion: Patients from PTB graft group showed comparable results as compared to the hamstrings group in terms of strenuous activity, highest level of activity, rising from a chair and kneeling and squatting on functional outcomes. Keywords: Anterior Cruciate Ligament, Patellar Auto-graft, Hamstring Auto-graft, Bone Graft.